FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA LEMBAGA PERKREDITAN DESA (LPD) PERIODE 2019-2021 DI KECAMATAN MENGWI - Ni Luh Laksmi Rahmantari; Made Putri Ariasih; Ni Komang Mela Tri Utari (Nusantara Hasana Journal, 2022)
This study aims to determine the factors that affect profitability in mengwi district LPD which is observed based on productive assets, third party funds and company size for the 2019-2021 period. The population in this study was as many as 38 Village Credit Institutions in Mengwi District which had been recorded in the LPLPD of Badung Regency and the samples in this study used the purposive sampling method of 30 LPD with a total of 90 observations. Technical data analysis using multiple regression analysis using IBM SPSS Statistics 25. The results of the study obtained that productive assets have a significant positive effect on profitability in lpd Mengwi District. Third-party funds have a significant positive effect on profitability in the Mengwi Subdistrict LPD. The size of the company has a positive effect on profitability in the Mengwi District LPD. Productive assets, third party funds and company size have a significant positive effect on the profitability of LPD Kecamtan Mengwi.